Design of FTTH network to Gregorio Albarracin Lanchipa district, Tacna - Rios De La Cruz, Ernesto Antonio (2020)
The objective of this research was design an access network with FTTH technology to distribute broadband services in Gregorio Albarracín Lanchipa district, in Tacna. The technical characteristics and benefits of FTTH technology with the GPON standard are described. This research work aims to propose a solution to the problem of last mile access to the district's telecommunications services, 3034 users or subscribers located in the housing associations of the Viñani pampas are selected. This external plant network consists of the distribution network, access network and termination network architecture, as well as the supply network from the internet provider. A mapping was carried out to collect information regarding the location of the network of electricity distribution poles and thus to know the location of the ADSS fiber optic cable route in the district, location of the optical dividers and equipment to be used. With the information collected, the calculation of the optical budget was made, the required bandwidth and the active and passive equipment to be used were determined